The Role Of Loanwords In The Modern Russian Language (Eurasian Research Bulletin, 2026)
This Article Examines The Role Of Loanwords In The Modern Russian Language, Their Impact On The Development Of The Lexical System, And Their Functional Characteristics Across Various Spheres Of Communication. It Analyzes The Primary Sources Of Loanwords, The Reasons For Their Emergence, And The Positive And Negative Aspects Of The Linguistic Borrowing Process. Particular Attention Is Paid To The Influence Of Globalization, Information Technology, And Intercultural Communication On The Active Expansion Of The Russian Lexicon Through Foreign Words. The Article Concludes That Loanwords Are A Significant Factor In Linguistic Development And Reflect Socio-Cultural Changes Within Society